Automatic Lung Segmentation and Quantification of Aeration in Computed Tomography of the Chest Using 3D Transfer Learning - Maiello, Lorenzo; Ball, Lorenzo; Micali, Marco; Iannuzzi, Francesca; Scherf, Nico; Hoffmann, Ralf-Thorsten; Gama de Abreu, Marcelo; Pelosi, Paolo; Huhle, Robert (Frontiers in Physiology, 2022)
Background: Identification of lung parenchyma on computer tomographic (CT) scans in the research setting is done semi-automatically and requires cumbersome manual correction. This is especially true in pathological conditions, hindering the clinical application of aeration compartment (AC) analysis. Deep learning based algorithms have lately been shown to be reliable and time-efficient in segmenting pathologic lungs. In this contribution, we propose a novel 3D transfer learning based approach to quantify lung volumes, aeration compartments and lung recruitability. Methods: Two convolutional neural networks developed for biomedical image segmentation (uNet), with different resolutions and fields of view, were implemented using Matlab. Training and evaluation was done on 180 scans of 18 pigs in experimental ARDS (u2Net_{Pig}) and on a clinical data set of 150 scans from 58 ICU patients with lung conditions varying from healthy, to COPD, to ARDS, and COVID-19 (u2Net_Human). One manual segmentations (MS) was available for each scan, being a consensus by two experts. Transfer learning was then applied to train u2Net_{Pig} on the clinical data set generating u2Net_Transfer. General segmentation quality was quantified using the Jaccard index (JI) and the Boundary Function score (BF). The slope between JI or BF and relative volume of non-aerated compartment (S_{JI} and S_{BF}) was calculated over data sets to assess robustness towards non-aerated lung regions. Additionally, the relative volume of ACs and lung volumes (LV) were compared between automatic and MS. Results: On the experimental data set, u2Net_{Pig} resulted in JI=0.892 [0.88:091] (median [inter-quartile range]), BF=0.995 [0.98:1.0] and slopes S_JI=-0.2 {95% conf.int. -0.23:-0.16} and S_{BF}=-0.1{-0.5:-0.06}. u2Net_Human showed similar performance compared to u2Net_Pig in JI, BF but with reduced robustness S_JI=-0.29{-0.36:-0.22} and S_BF=-0.43{-0.54:-0.31}. Transfer learning improved overall JI=0.92 [0.88:0.94], P<0.001, but reduced robustness S_JI=-0.46{-0.52:-0.40}, and affected neither BF=0.96 [0.91:0.98] nor S_{BF}=-0.48{-0.59:-0.36}. u2Net_Transfer improved JI compared to u2Net_Human in segmenting healthy(P=0.008), ARDS(P<0.001) and COPD(P=0.004) patients but not in COVID-19 patients(P=0.298). ACs and LV determined using u2Net_Transfer segmentations exhibited <5% volume difference compared to MS. Conclusion: Compared to manual segmentations, automatic uNet based 3D lung segmentation provides acceptable quality for both clinical and scientific purposes in the quantification of lung volumes, aeration compartments and recruitability.